Prioritizing Shark, Ray, and Chimaera Conservation in Rapidly Changing Polar Waters - Vanessa B. Bettcher; Amanda Batlle‐Morera; Peter M. Kyne; Ryan Charles; Emiliano García‐Rodríguez; Christoph A. Rohner; Asia O. Armstrong; Margaret O’Leary Amsler; Natalia V. Chernova; Brynn M. Devine; Andrey V. Dolgov; Meghan M. Donovan; et al. (Global Change Biology, 2026)
Climate‐driven alterations in sea‐ice dynamics and shifting fishing activity are reshaping ecosystems across the Arctic and Antarctic, yet conservation‐relevant information for chondrichthyans (sharks, rays, and chimaeras) remains limited. We present the first assessment of Important Shark and Ray Areas (ISRAs) across Polar Waters, integrating species distributions, extinction risk, critical habitat evidence, spatial protection coverage, apparent fishing effort (2013–2018 vs. 2019–2024), and sea‐ice concentration trends. Of 86 chondrichthyan species reported from Polar Waters, only 15 (17.4%) had sufficient evidence to meet the ISRA Criteria, and 28 (32.6%) are threatened with extinction. We identified 35 ISRAs (27 Arctic; 8 Antarctic) covering 0.75% of the Polar Waters region. ISRAs were delineated predominantly based on data from scientific fishing surveys and harvest fisheries. Most Antarctic ISRAs were delineated under Criterion B—Range Restricted, reflecting endemism and scarce life‐history evidence. Major knowledge gaps persist, particularly for highly adapted Polar Species (10 species) and deepwater taxa (72.1% of regional chondrichthyan fauna). Between 2013 and 2024, the spatial footprint of fishing expanded in both poles for trawlers and longliners, despite stable or declining fishing hours in some fleets. Concurrent areas of increasing fishing effort and decreasing sea‐ice concentration remained minimal. However, apparent fishing effort overlapped with most ISRAs, indicating ongoing fishing pressure in critical habitats. Marine Protected Area (MPA) coverage remains uneven: 8.2% of Arctic ISRA spatial extent overlaps MPAs (0.8% no‐take), compared with 43.8% in the Antarctic (14.8% no‐take), with insufficient effective coverage in areas beyond national jurisdiction. These results reveal substantial mismatches between chondrichthyan critical habitats, fishing exposure, and existing protection measures. Integrating ISRAs into existing management frameworks, such as Target 3 of the Global Biodiversity Framework, High Seas Treaty mechanisms, and fisheries governance bodies, will be essential to safeguard vulnerable polar chondrichthyans as sea‐ice concentration declines and exposure risk increases.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Role of funders in embedding tests in conservation practice - Rebecca K. Smith; Nancy Ockendon; Nida Al‐Fulaij; Alessandro Badalotti; Rachel Beattie; James Byrne; Sophia Cooke; Tiago de Zoeten; Winifred F. Frick; Stephan M. Funk; Douglas Gibbs; Lauren Gupta; et al. (Conservation Biology, 2026)
Effective conservation practice requires decisions based on reliable and relevant evidence, but significant gaps in the evidence base exist. Incorporating well‐designed tests of the effectiveness of interventions for biodiversity in conservation projects is one of the best ways to scale up the rate of evidence generation. Funders of conservation projects are uniquely positioned to support and incentivize such tests as part of the grant‐making process. Using a structured process, as 25 conservation funders and members of Conservation Evidence, we identified means of improving the effectiveness of the work funded through the support of enhanced evidence generation. We identified 11 approaches through which funders can support embedding testing, ranging from encouraging inclusion of a test in the project proposal, to designating separate funds for incorporating a test, to supporting an external testing unit to provide training and advice. The appropriate approaches vary depending on the scale, process, and type of funding. Barriers to supporting testing and potential solutions were discussed, barriers such as a lack of skills to check tests are appropriate and well designed and the additional time needed to develop, implement, and see outcomes of tests and differing types of projects. By encouraging testing of actions as part of conservation practice (where appropriate), funders will ultimately facilitate a stronger evidence base for more effective decision‐making and better outcomes for nature and society.

Diversity and functional group composition drive biogeographic patterns in marine biogenic structural complexity - Dean S. Janiak; Matthew A. Whalen; David R. Branson; Soledad Álvarez; Gail V. Ashton; Nicholas M. Bartkowiak; Simon J. Brandl; João Canning‐Clode; Jordan M. Casey; Max C. N. Castorani; Carolina César‐Ávila; Rachel Collin; et al. (Ecology, 2026)
Biogenic structural complexity is a key driver of biodiversity and ecosystem functioning, yet its ecological and environmental determinants remain poorly understood across broad biogeographic scales. Here, we conducted standardized 90‐day field experiments at 16 coastal sites, spanning a 41‐degree latitudinal gradient, using naturally assembled marine fouling communities on settlement panels. We measured rugosity as our metric of biogenic structural complexity and modeled its relationship with species richness, community composition, community growth rates, and abiotic conditions (salinity and temperature). Species richness increased with temperature and salinity and declined with latitude, with more diverse communities exhibiting greater biogenic complexity due to increased morphological variation. At high‐latitude sites, low‐diversity communities dominated by arborescent bryozoans also had increased complexity. Structural equation models showed that abiotic conditions influenced growth and composition, which in turn shaped complexity. Warmer, saltier sites promoted richness‐driven complexity, while colder conditions favored structurally important dominant taxa. We found that biodiversity is important not only as a beneficiary of complexity but also as a contributor to complexity itself within fouling communities. Our results also demonstrate that both species richness and functional group identity regulate biogenic complexity across environmental gradients, underscoring biodiversity's role in supporting ecosystem structure and resilience in the face of increasing global change. Understanding these relationships is essential for biodiversity conservation and the management of marine ecosystems facing increasing anthropogenic pressures.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Food limitation erodes the thermal tolerance of larvae in an ecologically influential marine herbivore - Maya J. Munstermann; Sam E. Karelitz; Rachele Ferraro; Laura Rogers‐Bennett; Rachel D. Simons; Daniel K. Okamoto (Ecology, 2026)
Biologists often use organismal thermal tolerance to help explain or forecast responses of populations to climate change. Yet many studies quantify thermal tolerance under isolated laboratory conditions despite extreme events, such as heatwaves, often coinciding with other stressors such as nutrient or food limitation. These oversights may be consequential as recent theory suggests thermal tolerance itself can be fundamentally altered by food limitation. Here, we experimentally test how food limitation (500–10,000 cells mL −1 ) affects long‐term survival, development, and growth across a present‐day range of temperatures (10–20°C) in the most sensitive life stages of an important marine herbivore, purple sea urchins ( Strongylocentrotus purpuratus ). We show food limitation substantially erodes thermal tolerance in terms of survival, but when provided ample food, larvae exhibited robust survival across temperatures currently experienced by larvae in nature. Reductions in food however lowered optimal survival temperatures and shifted survival thresholds to those conditions observed during recent marine heatwaves. These results are consistent with the “metabolic meltdown” hypothesis—shifting optima and upper limits to cooler temperatures—and illustrate how present‐day warming coupled with lower productivity may lead to substantial, unexpected declines in larval survival and recruitment. In contrast to survival, developmental rates and time to metamorphic competency, which ranged from 21 to 61 days, were driven largely by temperature with little impact of food concentration. Our findings relate to historical observations of declines in larval supply at the southern edge of the species range. Overall, these results have broad‐reaching implications beyond sea urchin populations as sea urchin herbivory is known to control productivity of kelp forest communities. We provide evidence of how laboratory derived thermal reaction norms can be coupled with ecologically relevant food concentrations to inform unexpected vital rate declines of sensitive life stages in a changing climate.

Consumer knowledge of and engagement with traditional takeaway and dark kitchen food outlets - Jordan D. Beaumont; Helen Martin; Claire Wall; Jo Pearce; Rachel Rundle; Simon Bowles; David Harness; Lucie Nield (Appetite, 2025)

Selection on genome‐wide gene expression plasticity of rice in wet and dry field environments - Elena Hamann; Simon C. Groen; Taryn S. Dunivant; Irina Ćalić; Colleen Cochran; Rachel Konshok; Michael D. Purugganan; Steven J. Franks (Molecular Ecology, 2025)
Gene expression can be highly plastic in response to environmental variation. However, we know little about how expression plasticity is shaped by natural selection and evolves in wild and domesticated species. We used genotypic selection analysis to characterize selection on drought‐induced plasticity of over 7,500 leaf transcripts of 118 rice accessions (genotypes) from different environmental conditions grown in a field experiment. Gene expression plasticity was neutral for most gradually plastic transcripts, but transcripts with discrete patterns of expression showed stronger selection on expression plasticity. Whether plasticity was adaptive and co‐gradient or maladaptive and counter‐gradient varied among varietal groups. No transcripts that experienced selection for plasticity across environments showed selection against plasticity within environments, indicating a lack of evidence for costs of adaptive plasticity that may constrain its evolution. Selection on expression plasticity was influenced by degree of plasticity, transcript length and gene body methylation. We observed positive selection on plasticity of co‐expression modules containing transcripts involved in photosynthesis, translation and responsiveness to abiotic stress. Taken together, these results indicate that patterns of selection on expression plasticity were context‐dependent and likely associated with environmental conditions of varietal groups, but that the evolution of adaptive plasticity would likely not be constrained by opposing patterns of selection on plasticity within compared to across environments. These results offer a genome‐wide view of patterns of selection and ecological constraints on gene expression plasticity and provide insights into the interplay between plastic and evolutionary responses to drought at the molecular level.

A record of the transition from foreland to piggy-back basin from the western Churia Range in Central Nepal: Evidence from luminescence dating and geomorphology - Donny R. Wahyudi; Hugh D. Sinclair; Simon M. Mudd; Rachel K. Smedley; Emma L.S. Graf (Geomorphology, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Strengthening global-change science by integrating aeDNA with paleoecoinformatics - John W. Williams; Trisha L. Spanbauer; Peter D. Heintzman; Jessica Blois; Eric Capo; Simon J. Goring; Marie-Eve Monchamp; Laura Parducci; Jordan M. Von Eggers; Inger Greve Alsos; Chris Bowler; Marco J.L. Coolen; et al. (Trends in Ecology & Evolution, 2023)

Regulation of a surface chlorophyll hotspot by wind-driven upwelling and eddy circulation in the Santa Barbara Channel, Southern California - Rachel D. Simons; Dylan Catlett (Progress in Oceanography, 2023)

Within-region replication of late Holocene relative sea-level change: An example from southern New England, United States - Rachel B. Stearns; Simon E. Engelhart; Andrew C. Kemp; Troy D. Hill; Matthew J. Brain; D. Reide Corbett (Quaternary Science Reviews, 2023)

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Creating a space for place and multidimensional well-being: lessons learned from localizing the SDGs - Eleanor J. Sterling; Puaʻala Pascua; Amanda Sigouin; Nadav Gazit; Lisa Mandle; Erin Betley; John Aini; Simon Albert; Sophie Caillon; Jennifer E. Caselle; Samantha H. Cheng; Joachim Claudet; et al. (Sustainability Science, 2020)
Achieving sustainable development globally requires multilevel and interdisciplinary efforts and perspectives. Global goals shape priorities and actions at multiple scales, creating cascading impacts realized at the local level through the direction of financial resources and implementation of programs intended to achieve progress towards these metrics. We explore ways to localize global goals to best support human well-being and environmental health by systematically comparing the UN Sustainable Development Goals (SDGs) with regionally-derived well-being dimensions that encompass components of social–ecological resilience across the Pacific Islands. Our research shows that, in the context of the Pacific, there are overlaps but also significant gaps between regional conceptions of well-being and the globally-derived SDGs. Some dimensions, related to human health and access to infrastructure and finances, are well represented in the SDGs. Other dimensions of high importance when localizing perspectives of well-being, such as those regarding connections between and across people and place and Indigenous and local knowledge, are not. Furthermore, internationally generated indicators may result in trade-offs and measurement challenges in local contexts. Creating space for place-based values in global sustainability planning aligns with international calls for transformational changes needed to achieve global goals. We identify challenges in applying SDG indicators at the local level and provide lessons learned to foster equitable and holistic approaches and outcomes for sustainability.

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

Predicting personality from network-based resting-state functional connectivity - Alessandra D. Nostro; Veronika I. Müller; Deepthi P. Varikuti; Rachel N. Pläschke; Felix Hoffstaedter; Robert Langner; Kaustubh R. Patil; Simon B. Eickhoff (Brain Structure and Function, 2018)

Scale-specific drivers of kelp forest communities - Thomas Lamy; Daniel C. Reed; Andrew Rassweiler; David A. Siegel; Li Kui; Tom W. Bell; Rachel D. Simons; Robert J. Miller (Oecologia, 2018)

A global synthesis of the effects of diversified farming systems on arthropod diversity within fields and across agricultural landscapes - Elinor M. Lichtenberg; Christina M. Kennedy; Claire Kremen; Péter Batáry; Frank Berendse; Riccardo Bommarco; Nilsa A. Bosque‐Pérez; Luísa G. Carvalheiro; William E. Snyder; Neal M. Williams; Rachael Winfree; Björn K. Klatt; et al. (Global Change Biology, 2017)
Agricultural intensification is a leading cause of global biodiversity loss, which can reduce the provisioning of ecosystem services in managed ecosystems. Organic farming and plant diversification are farm management schemes that may mitigate potential ecological harm by increasing species richness and boosting related ecosystem services to agroecosystems. What remains unclear is the extent to which farm management schemes affect biodiversity components other than species richness, and whether impacts differ across spatial scales and landscape contexts. Using a global metadataset, we quantified the effects of organic farming and plant diversification on abundance, local diversity (communities within fields), and regional diversity (communities across fields) of arthropod pollinators, predators, herbivores, and detritivores. Both organic farming and higher in‐field plant diversity enhanced arthropod abundance, particularly for rare taxa. This resulted in increased richness but decreased evenness. While these responses were stronger at local relative to regional scales, richness and abundance increased at both scales, and richness on farms embedded in complex relative to simple landscapes. Overall, both organic farming and in‐field plant diversification exerted the strongest effects on pollinators and predators, suggesting these management schemes can facilitate ecosystem service providers without augmenting herbivore (pest) populations. Our results suggest that organic farming and plant diversification promote diverse arthropod metacommunities that may provide temporal and spatial stability of ecosystem service provisioning. Conserving diverse plant and arthropod communities in farming systems therefore requires sustainable practices that operate both within fields and across landscapes.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Connectivity structures local population dynamics: a long‐term empirical test in a large metapopulation system - Max C. N. Castorani; Daniel C. Reed; Filipe Alberto; Tom W. Bell; Rachel D. Simons; Kyle C. Cavanaugh; David A. Siegel; Peter T. Raimondi (Ecology, 2015)
Ecological theory predicts that demographic connectivity structures the dynamics of local populations within metapopulation systems, but empirical support has been constrained by major limitations in data and methodology. We tested this prediction for giant kelp Macrocystis pyrifera , a key habitat‐forming species in temperate coastal ecosystems worldwide, in southern California, USA. We combined a long‐term (22 years), large‐scale (~500 km coastline), high‐resolution census of abundance with novel patch delineation methods and an innovative connectivity measure incorporating oceanographic transport and source fecundity. Connectivity strongly predicted local dynamics (well‐connected patches had lower probabilities of extinction and higher probabilities of colonization, leading to greater likelihoods of occupancy) but this relationship was mediated by patch size. Moreover, the relationship between connectivity and local population dynamics varied over time, possibly due to temporal variation in oceanographic transport processes. Surprisingly, connectivity had a smaller influence on colonization relative to extinction, possibly because local ecological factors differ greatly between extinct and extant patches. Our results provide the first comprehensive evidence that southern California giant kelp populations function as a metapopulation system, challenging the view that populations of this important foundation species are governed exclusively by self‐replenishment.

The Role of Nitrogen Deposition in Widespread Plant Community Change Across Semi-natural Habitats - Chris D. Field; Nancy B. Dise; Richard J. Payne; Andrea J. Britton; Bridget A. Emmett; Rachel C. Helliwell; Steve Hughes; Laurence Jones; Steven Lees; Jonathan R. Leake; Ian D. Leith; Gareth K. Phoenix; et al. (Ecosystems, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

ABO blood group and risk of epithelial ovarian cancer within the Ovarian Cancer Association Consortium - Elizabeth M. Poole; Margaret A. Gates; Brigit A. High; Stephen J. Chanock; Daniel W. Cramer; Julie M. Cunningham; Brooke L. Fridley; Simon A. Gayther; Ellen L. Goode; Edwin S. Iversen; Jolanta Lissowska; Rachel T. Palmieri Weber; et al. (Cancer Causes & Control, 2012)

Impacts of atmospheric nitrogen deposition: responses of multiple plant and soil parameters across contrasting ecosystems in long‐term field experiments - Gareth K. Phoenix; Bridget A. Emmett; Andrea J. Britton; Simon J. M. Caporn; Nancy B. Dise; Rachel Helliwell; Laurence Jones; Jonathan R. Leake; Ian D. Leith; Lucy J. Sheppard; Alwyn Sowerby; Michael G. Pilkington; et al. (Global Change Biology, 2012)
Atmospheric nitrogen ( N ) deposition is a global and increasing threat to biodiversity and ecosystem function. Much of our current understanding of N deposition impacts comes from field manipulation studies, although interpretation may need caution where simulations of N deposition (in terms of dose, application rate and N form) have limited realism. Here, we review responses to simulated N deposition from the UKREATE network, a group of nine experimental sites across the UK in a diversity of heathland, grassland, bog and dune ecosystems which include studies with a high level of realism and where many are also the longest running globally on their ecosystem type. Clear responses were seen across the sites with the greatest sensitivity shown in cover and species richness of bryophytes and lichens. Productivity was also increased at sites where N was the limiting nutrient, while flowering also showed high sensitivity, with increases and declines seen in dominant shrub and forb species, respectively. Critically, these parameters were responsive to some of the lowest additional loadings of N (7.7–10 kg ha −1 yr −1 ) showing potential for impacts by deposition rates seen in even remote and ‘unpolluted’ regions of E urope. Other parameters were less sensitive, but nevertheless showed response to higher doses. These included increases in soil % N and ‘plant available’ KCl extractable N , N cycling rates and acid–base status. Furthermore, an analysis of accumulated dose that quantified response against the total N input over time suggested that N impacts can ‘build up’ within an ecosystem such that even relatively low N deposition rates can result in ecological responses if continued for long enough. Given the responses have important implications for ecosystem structure, function, and recovery from N loading, the clear evidence for impacts at relatively low N deposition rates across a wide range of habitats is of considerable concern.

Zooplankton retention in the estuarine transition zone of the St. Lawrence Estuary - Rachel D. Simons; Stephen G. Monismith; Ladd E. Johnson; Gesche Winkler; François J. Saucier (Limnology and Oceanography, 2006)
We used a three‐dimensional physical‐biological model consisting of a Eulerian circulation model and a Lagrangian particle‐tracking model, which included vertical sinking and swimming, to explore zooplankton retention in the estuarine transition zone of the St. Lawrence Estuary (SLETZ). To test the accuracy of the model, the results were temporally and spatially compared to a passive scalar released simultaneously in the circulation model and to field data for zebra mussel veligers. The model was then used to study the effects of baroclinic density‐driven flow, vertical sinking and swimming, and tidal vertical migration on retention of simulated zooplankton. Baroclinic flow, created by longitudinal and lateral salinity gradients, was a critical part of retention in the SLETZ. In the presence of baroclinic flow, vertical sinking and swimming speeds of $0.2 mm s21 had a large effect on the residence time of the simulated zooplankton as a result of gravitational circulation. Tidal vertical migration—a pattern of upward movement on flood and downward movement on ebb—was a viable retention mechanism for the SLETZ, and its effectiveness was amplified by baroclinic flow. As the speed of tidal vertical migration increased, the simulated zooplankton were concentrated in smaller areas of the SLETZ and moved further upstream.

Evidence that Soil Carbon Pool Determines Susceptibility of Semi-Natural Ecosystems to Elevated Nitrogen Leaching - Christopher D. Evans; Brian Reynolds; Alan Jenkins; Rachel C. Helliwell; Christopher J. Curtis; Christine L. Goodale; Robert C. Ferrier; Bridget A. Emmett; Michael G. Pilkington; Simon J. M. Caporn; Jacky A. Carroll; David Norris; et al. (Ecosystems, 2006)

On the utility of data from the International HapMap Project for Australian association studies - Jim Stankovich; Charles J. Cox; Rachel B. Tan; Douglas S. Montgomery; Stewart J. Huxtable; Justin P. Rubio; Margaret G. Ehm; Laura Johnson; Helmut Butzkueven; Trevor J. Kilpatrick; Terence P. Speed; Allen D. Roses; et al. (Human Genetics, 2006)